Persuasive Communication Of The Ruang Pangan Community In Food Rescue Programs - Rosa Destriani; Hanindyalaila Pienrasmi; Noning Verawati (Universitas Dharmawangsa Medan, 2026)
Food waste has become a serious environmental and social issue in Indonesia, encouraging the emergence of community-based initiatives focused on food rescue. This study was conducted to examine how persuasive communication is implemented by the Ruang Pangan community in the Food rescue program to build awareness and understanding among partners and beneficiaries. The research employed a qualitative descriptive approach. Data were collected through in-depth interviews with key informants, including founders, campaign teams, partners, and beneficiaries, as well as observation and documentation. The findings show that persuasive communication in the Food rescue program is carried out through a gradual and contextual process that emphasizes clarity of messages, audience-oriented language, and direct interaction. Communication with partners focuses on introducing the program’s concept, work mechanism, and social benefits, supported by the use of social media as an initial communication medium and followed by direct meetings to strengthen understanding and trust. Meanwhile, communication with beneficiaries is conducted through face-to-face interaction accompanied by simple educational messages that explain the purpose of food rescue, the origin of surplus food, and its environmental impact. As a result, beneficiaries do not merely receive food assistance but also gain awareness of the value of food and the importance of reducing food waste. Overall, the study concludes that persuasive communication plays a significant role in shaping shared understanding and meaningful participation in community-based food rescue initiatives, contributing to the development of communication studies in the context of social and environmental campaigns.